PELATIHAN PENGENALAN DASAR PENGEDITAN KONTEN VIDEO DAN TATA CARA PENGUNGGAHAN KONTEN KE MEDIA SOSIAL - fery, fery; Nurnaningsih; Muzakir, Subhan (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2025)
Video content editing is a skill that is increasingly important in the current digital era, especially with the increasing use of social media platforms as a means of promotion and communication, both for personal purposes and for business and entertainment purposes. This article aims to provide a basic introduction to video editing and discuss effective and important steps and strategies in the process of creating and uploading content to social media. Good video management will have a significant impact in increasing audience engagement and achieving desired goals.